THE LIPSTICK EFFECT AS A MICROECONOMIC RESPONSE: A STUDY OF GEN Z CONSUMER BEHAVIOR IN THE DIGITAL CRISIS ERA - Destina Paningrum; Annisa Indah Mutiasari; Anggit Dyah Kusumastuti; Diah Anggie Navita (LPPM UNIVERSITAS BINA INSAN, 2026)
The lipstick effect phenomenon currently represents consumers' psychological response, which tends to maintain consumption of small-scale luxury goods like cosmetics even in challenging economic conditions. This behavior is seen as a form of emotional compensation and an individual's coping strategy amidst financial pressure. In the context of microeconomics, this kind of consumption behavior reflects consumers' adaptive dynamics in response to economic uncertainty, particularly in the digital age, which also influences consumption patterns. This study aims to analyze the social and psychological determinants that influence Generation Z's consumption behavior in purchasing small cosmetic products as a form of the lipstick effect during the digital crisis. The research approach used is quantitative with a survey method via online questionnaires. The research respondents are Gen Z individuals who are active on social media and regularly purchase cosmetic products. The independent variables in this study include perceptions of the economic crisis, psychological motivation for consumption, and digital lifestyle, while the dependent variable is small luxury consumption behavior. The data obtained were analyzed using multiple linear regression techniques to test the significant influence of each independent variable on the dependent variable. The expected outcome of this research is a deeper understanding of the factors that trigger the lipstick effect in young people, as well as its strategic implications for cosmetic industry players and policymakers in the field of consumer microeconomics. This research is expected to contribute academically to the development of consumer behavior theory during a crisis, while also serving as a basis for formulating marketing strategies relevant to the emotional and social characteristics of Generation Z